Exploring the deactivation mechanism of human β2 adrenergic receptor by accelerated molecular dynamic simulations - Chen, Jianzhong; Wang, Jian; Zeng, Qingkai; Wang, Wei; Sun, Haibo; Wei, Benzheng (Frontiers in Molecular Biosciences, 2022)
The β2 adrenergic receptor (β2AR), one of important members of G protein coupled receptors (GPCRs), has been suggested as an important target for cardiac and asthma drugs. Two replicas of Gaussian accelerated molecular dynamics (GaMD) simulations are performed to explore deactivation mechanism of the β2AR bound by three different substrates, including the agonist (P0G), antagonist (JTZ) and inverse agonist (JRZ). Simulation results indicate that the Gs protein is needed to stabilize the active state of the β2AR. Without Gs protein, the receptor could transit from the active state toward the inactive state. During the transition process, helix TM6 moves toward TM3 and TM5 in geometric space and TM5 shrinks upwards. The intermediate state is captured during the transition process of the active β2AR toward the inactive one, moreover the changes in hydrophobic interaction networks between helixes TM3, TM5 and TM6 and the formation of a salt bridge between residues Arg3.50 and Glu6.30 drive the transition process. We expect that this finding can provide energetic basis and molecular mechanism for further understanding the function and target roles of the β2AR.